Anisakid nematodes from the largehead hairtail fish (Trichiurus lepturus) from the northern coast of Java, Indonesia - Eko Setyobudi; Murwantoko Murwantoko; Alusia Melanita Ria Utami; Rizka Fauziana Syarifah (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Setyobudi E, Murwantoko, Utami AMR, Syarifah RF. 2023. Anisakid nematodes from the largehead hairtail fish (Trichiurus lepturus) from the northern coast of Java, Indonesia. Biodiversitas 24: 1560-1568. Hairtail fish has been frequently reported to be infected by anisakid nematodes. This study aims to determine the presence of anisakid nematodes on the large-head hairtail fish (Trichiurus lepturus) from the northern coast of the Java Sea, Indonesia. In total, 306 hairtail fish were collected from the northern coast of Java. Each fish sample was measured its length and weighed, then dissected to examine the presence of anisakid nematode. The anisakid larva examination was conducted in the body cavity, internal organs, digestive tract, and muscles. The anisakid nematodes found were then separated and grouped based on morphological appearance, namely body color and size. Selected samples from each anisakid group and sampling location were extracted and identified molecularly by the direct sequencing method. The findings showed that the larvae of anisakid nematodes infect the T. lepturus with different prevalence and average intensity at each location (P: 38.0-100%, MI: 3.33-42.88 larvae/ind.). Mostly anisakid larvae were found in the body cavity and were not found in the muscle. Most of the T. lepturus from the northern coasts of Cirebon and Pati were infected with anisakid at low intensity (?5 larvae/individual). The high intensity of anisakid larval infection was shown by the hairtail originating from Rembang and Tuban (>20 larvae/ind.). Molecular identification showed that three anisakids were isolated from hairtails from the northern coast of Java, namely Anisakis typica, Hysterothylacium amoyense, and Raphidascaris lophii. Information on anisakid species and their distribution is important as a reference for fish handling and processing, the assessment of the human health risk, and the development of these nematodes as biological tags.